How to Be New Generation Entrepreneurs in Thailand 4.0 - ทัฬหกรณ์ ทิบดี; จันทึก ธีระวัฒน์ (RMUTT Global Business and Economics Review, 2017)
When considering on the current business world that is full of high competition, Thailand’s industry that is often in the form of Mass Production cannot be developed or driven further or to be equal with those developed countries, i.e., Thailand’s industry is not both low cost production or under the framework of science, technology, innovations, and creativity. Accordingly, to strengthen Thailand’s economy and industry, the conce4pt of New Generation Entrepreneurs in Thailand 4.0 was created, especially for Small and Medium-sized Enterprises (SMEs) that are the main pillar supporting domestic economy. As a result, it is necessary for these entrepreneurs to be given knowledge and reinforced with skills on management, creative product design or planning with the government as the intermediary to coordinate and support entrepreneurs on funding as well as adjust laws to be flexible for them or business benefits, seek for marketing channels, and providing experts or consultants on various dimensions. The model of the process on creating new generation entrepreneurs in Thailand 4.0 is as follows: 1) new generation entrepreneurs can approach sources of funding efficient; 2) new generation entrepreneurs were reinforced with knowledge on business start-up and business planning; 3) new generation entrepreneurs were promoted on product development, branding, and creative marketing; 4) new generation entrepreneurs were promoted on domestic marketing channels; and 5) new generation entrepreneurs were driven to export their products to foreign markets.